2021
DOI: 10.1101/2021.04.01.437973
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spontaneous Neural Activity Changes after Bariatric Surgery: a resting-state fMRI study

Abstract: Background: Metabolic disorders associated with obesity could lead to alterations in brain structure and function. Whether these changes can be reversed after weight loss is unclear. Bariatric surgery provides a unique opportunity to address these questions because it induces marked weight loss and metabolic improvements which in turn may impact the brain in a longitudinal fashion. Previous studies found widespread changes in grey matter (GM) and white matter (WM) after bariatric surgery. However, findings reg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Taken together, these findings revealed a possible underlying pathophysiology between restrained eating and the risk of weight gain (Dong et al, 2015). In addition, the ReHo method was used to study the effect of bariatric surgery-induced weight loss on brain activity (Zeighami et al, 2021). Zeighami et al (2021) observed a significant increase in ReHo in the visual cortex, medial temporal gyrus, and DLPFC at 4 months after surgery.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Taken together, these findings revealed a possible underlying pathophysiology between restrained eating and the risk of weight gain (Dong et al, 2015). In addition, the ReHo method was used to study the effect of bariatric surgery-induced weight loss on brain activity (Zeighami et al, 2021). Zeighami et al (2021) observed a significant increase in ReHo in the visual cortex, medial temporal gyrus, and DLPFC at 4 months after surgery.…”
Section: Introductionmentioning
confidence: 84%
“…Although neuroimaging studies on obesity have identified obesity-related abnormalities in a wide range of brain areas, these abnormalities can be reshaped after weight loss by CER involving reward cognitive control and sensory processing (Carnell et al, 2012;Zhang et al, 2015;Belaïch et al, 2017;Zeighami et al, 2021). Amanda et al used the method of caloric restriction for weight loss in obese patients for 3 months and found that prefrontal cortical activation influences health behavior changes in the context of an intervention to produce weight loss and manage obesity (Szabo-Reed et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain age for each participant in the ABCD dataset was estimated based on imaging features and the model described above. For each participant, we calculated a difference between chronological age and brain age – delta age [62, 63]. Finally, we correlated delta age with BMI-PRS (corrected for first 20 genetic principal components).…”
Section: Methodsmentioning
confidence: 99%